ANALISIS HAMBATAN SAMPING DI SEGMEN KULINER TAMAN TUNGGAL SANGOMANG KOTA PALANGKA RAYA - Ega Saputra Harahap; Desi Riani; Supiyan Supiyan (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2025)
Side friction often found in several side of roads, especially on the other side of the road between incoming and outgoing activity vehicle segment of the road, pedestrians, parking and vehicle stops, as well as non-motorized transport across the road segment. Side friction is what often causes congestion on roads. Therefore the Yos Sudarso road in Palangka Raya, problem will arise that affect the performance of the road section. This study was conducted to determine how much influence the side friction of the road section on the performance of the road on Yos Sudarso Road Taman Kuliner Tunggal Sangomang section Palangka Raya City. The method used in this study uses PKJI 2014. To finde volume, capacity, service level and road performance that are affected by side friction on the roads. From the research results obtained traffic volume (Q), at peak hour on Saturday 26 November 2022 at 6.00 – 7.00 PM obtained Q = 816 skr/hour amount of side frictions obtained 102 with class of side friction low (R). from the results of the performance of the road segment, obtained capacity of Yos Sudarso road is 3457,08 skr/hour. There was a decrease capacity due to side friction to 2965, 25 skr/hour. And the degree of saturation (DJ) reach 0,32 which is includedin the level of service for road B with a stable traffic flow but the operating flow,but the operating speed is starting to be limited due to traffic conditions